A methodology for designing communication protocols. - Singh, Gurdip (Computer communication review.)
We propose a compositional technique for designing protocols. The technique involves specifying constraints between the events of the component protocols. A constraint may either require synchronization between certain events of the component protocols or may require inhibiting an event in one protocol on the occurrence of an event in another component protocol. We find both types of constraints useful in composing protocols. We demonstrate the applicability of the technique by deriving several protocols. The technique facilitates modular design and verification. Our technique, in conjunction with the sequential composition technique, can be used to design complex protocols.